Implementasi Pemahaman Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah Bagi Pelaku UMKM Di Kabupaten Purbalingga - Aning Fitriana (Universitas Nusantara PGRI Kediri, 2022)
This aims of this research is to provide evidence regarding the implementation of SAK EMKM. This research is a qualitative descriptive research,the data collected through questionnaires. The object of the research is the MSME business actors in Purbalingga district as a provider of accounting information as many as 100 respondents. The purpose of the research is to describe and analyze the understanding of MSME actors on the implementation of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in Purbalingga district. The results of this study indicate that business actors quite agree with the application of SAK EMKM to reports, business actors do not fully know SAK EMKM, and the use of accounting information in financial statements is still low.